Sir Michael Costa (1808-1884) - Zobel, George J., 1810-1881 (engraver):::Creator::::::::::::; Caldesi (photographer):::Contributor:::::::::::: (J. Mitchell; United Kingdom; London, 2020)
Mezzotint portrait engraving of Sir Michael Costa (1808-1884) by George Zobel, after a photograph by Caldesi, with facsimile of Costa's signature.